(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Simkova I. O. The current state of future bachelor-philologists training in bilingual interpreting in scientific and technical sphere. On the ground of analysis, contrast, and unification of educational-qualification characteristics, educational-professional programs, job description catalogue, and different foreign standards in interpreting the current state of future interpreters training in interpreting in scientific and technical sphere is considered in the article.